Towards a framework for identifying and measuring the benefits of accessibility - Daphne Federing; David Lewis (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
This paper (i) explains the motivation for articulating the benefits of accessibility; (ii) provides a narrative basis for articulating how accessibility affects economic and social life; and (iii) moves towards a framework for quantifying the benefits of accessibility. In examining laws, regulations and judicial proceedings in different nations, the paper finds that most view cost as a limiting factor on what public and private entities can be compelled to provide in relation to the accessibility of transportation, the built environment, employment, and services. This is so even in the context of constitutionally and legislatively enshrined human rights. The paper also finds that cost-benefit balancing is emerging as a necessary part of the accessibility governance framework. When addressing the specific application of accessibility rights, governments, regulatory bodies and courts around the world deal comprehensively with costs but fail to value important categories of benefit, such as the reduction of stigmatic harms, "option" benefits and "existence" value, and capability value. The paper describes progress towards a comprehensive narrative and analytical framework for describing and measuring such benefits.
Keywords: 330; Verkehrsinfrastruktur; Räumliche Erreichbarkeit; Behindertenpolitik; Behinderte; Ältere Menschen; Welt